Northern exposure Season 5 Disc 1 - Corbin, Barry 1940-; Geary, Cynthia; Ballard, Doug; Turner, Janine 1963-; Burrows, Darren E.; Morrow, Rob; Corbett, John 1961-; Cullum, John 1930-; Phillips, Peg; Miles, Elaine 1960-; Brand, Joshua; Falsey, John; et al. (Universal City, CA Universal Pictures, 2006)
Reunite with Dr. Joel Fleischman, Maggie, Chris, and the rest of the quirky residents of Cicely, Alaska, as the gang take on evil spirits, cannibalistic ancestors and the birth of a new resident.
Three doctors -- The mystery of the old curio shop -- Jaws of life -- Altered egos -- A river doesn't run through it.
Title from container and disc label.
Created by Joshua Brand and John Falsey.
Originally broadcast on television during the 1993-1994 season.
Set contains all 24 episodes from the fifth season.
"Music may differ from television version"--Container
Barry Corbin, Cynthia Geary, Doug Ballard, Janine Turner, Darren E. Burrows, Rob Morrow, John Corbett, John Cullum, Peg Phillips, Elaine Miles.
Keywords: Physician and patient -- Alaska -- Drama; Cities and towns -- Alaska -- Drama; Neighbors -- Alaska -- Drama; Man-woman relationships -- Alaska -- Drama; Alaska; Drama; Television comedies; Television programs; Video recordings for the hearing impaired; Television serials